2005
DOI: 10.1118/1.1852792
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gantry angle on megavoltage photon beam attenuation by a carbon fiber couch insert

Abstract: The use of rigid carbon fiber couch inserts in radiotherapy treatment couches is a well-established method of reducing patient set-up errors associated with couch sag. Several published studies have described such inserts as radiotranslucent with negligible attenuation of the radiation field. Most of these studies were conducted with the radiation field normally incident on the couch and there appears to be no evidence in the literature of the effect of the gantry angle on the extent of beam attenuation by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 7 publications
4
74
0
Order By: Relevance
“…Several authors have studied the effects of carbon fiber couchtops on surface dose 6 , 31 , 32 , 33 . The proximity of the patient to the couch means that the skin sparing effect is almost completely lost and surface doses increase to 85%–95% of that seen at normaldmax, and for FFF beams a similar pattern is observed.…”
Section: Discussionmentioning
confidence: 96%
“…Several authors have studied the effects of carbon fiber couchtops on surface dose 6 , 31 , 32 , 33 . The proximity of the patient to the couch means that the skin sparing effect is almost completely lost and surface doses increase to 85%–95% of that seen at normaldmax, and for FFF beams a similar pattern is observed.…”
Section: Discussionmentioning
confidence: 96%
“…They found that the largest beam attenuation occurred at beam entry angles of about 75° from normal incidence. McCormack et al (23) found the beam attenuation of a carbon fiber couch insert on the Elekta SLi linac ranged from 2% (normal incidence) to a maximum of approximately 9% (incidence at angle of 70° from vertical). Poppe et al (24) reported the attenuation of a carbon fiber tabletop for two energies: 1) 6 MV: 2.7% for 180° gantry angle and 3.2% for 150° gantry angle, and 2) 10 MV: 2.3% for 180° gantry angle and 2.4% for 150° gantry angle.…”
Section: Discussionmentioning
confidence: 99%
“…A “simple” solution reported by McCormack et al ( 9 ) calls for a fixed posterior oblique beam, using a correction factor based on the CAX attenuation to adjust the beam's MU. However, this process may not accurately predict the treatment couch's attenuation properties.…”
Section: Discussionmentioning
confidence: 99%
“…( 1 3 ) A number of investigations about the attenuation properties of different treatment couches have been reported. ( 4 9 ) The attenuation by carbon fiber couches was found to be less than 3% at normal incidence for 6 MV photon beams, depending on the couch design. ( 7 9 ) McCormack et al ( 9 ) demonstrated the effect of gantry angle on attenuation by a carbon fiber couch, ranging from 2% at normal incidence to 9% at 70° incidence for 6 MV photon beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation